Seismic Performance Analysis of Isolation Bearings Based on New Materials - Cao, Hanyang; Peng, Huanhai; Zhou, Zukun (Transactions on Engineering and Technology Research, 2024)
As a traditional isolation technology, isolation bearing technology has also experienced many innovative research. In order to ensure that buildings and infrastructure can successfully mitigate the seismic consequences of earthquakes, new materials for isolation bearings are being studied. This paper first introduces three new materials: high performance rubber material, shape memory alloy (SMA) material and electro-rheological fluid (ERF) material. Then, their application in isolation bearing is discussed, and their anti-seismic principle and performance are analyzed. Finally, it is concluded that the selection of different new materials for isolation bearings under different conditions can improve the seismic performance of buildings and infrastructure. The three new materials proposed in this study have their own advantages and potential applications in isolation bearings, which provide more innovative and feasible choices for the design of isolation bearings. The purpose of this paper is to improve the seismic performance of the isolation bearing and ensure the effectiveness of the isolation bearing in reducing the seismic effect during the earthquake event, so as to ensure the safety of human life and property.